Effect of bremelanotide on body weight of obese women: Data from two phase 1 randomized controlled trials. Issue 6 (15th March 2022) - Spana, Carl; Jordan, Robert; Fischkoff, Steven
Abstract: Aims: The melanocortin 4 receptor (MC4R) plays a central role in appetite regulation, and agonistic activity at this receptor promotes satiety. Results from two randomized controlled clinical trials examine the effects of bremelanotide's agonism at MC4R on caloric intake and body weight. Methods: Premenopausal women with a body mass index >30 kg/m 2 were studied in two phase 1, single‐centre, randomized, double‐blind, placebo‐controlled trials. Study A matched subjects 1:1 to receive subcutaneous placebo or bremelanotide three times daily for days 1‐15. Study B was a crossover trial with six distinct treatment sequences consisting of three 4‐day treatment periods, investigating once‐a‐day and twice‐a‐day exposure to bremelanotide versus placebo. Subjects received one of the three treatments twice‐daily during each period: 0 mg/0 mg, 2.5 mg/0 mg or 2.5 mg/2.0 mg bremelanotide. Body weight and food intake were recorded in detail daily. Adverse events were recorded throughout both studies. Results: In Study A, 27 of 30 bremelanotide subjects (90.0%) completed the trial and exhibited a significantly greater reduction in body weight after 16 days versus placebo [least squares mean difference (95% CI), −1.3 (−1.9 to −0.8) kg; p  < .0001]. Mean caloric intake in bremelanotide subjects was decreased versus placebo, with a magnitude of reduction of approximately 400 kcal/day throughout Study A ( p  < .01). In Study B, 15 of 27 subjects (55.6%) completed all three phases. Significantly greater reduction of mean body weight occurred in twice‐daily bremelanotide subjects versus placebo (1.7 vs. 0.9 kg, respectively, p  < .001). Total caloric intake reduction was significantly greater in the bremelanotide groups versus placebo (mean difference range: 398‐469 kcal; p  < .0001). Conclusions: Agonist activity at the MC4R may aid in reducing caloric intake and weight loss in obese women.